Comparing the consumption of musical and films online between Generations X and Y in Portugal and Spain - Trindade, G.; Duarte, A. (2019 14th Iberian Conference on Information Systems and Technologies (CISTI), 2019)
Numerous studies have been published evidencing the characteristics of Millennial generation (also known as Gen Y) by comparison with generation X or Gen X. The internet affirms itself as a differentiating factor and determinant of attitudes and behaviors. Considering the ease of access and the familiarity of Millennials, with the new technologies, it lacks analysis the preferences of use and consumption of music and films and television series, anchored in the Internet. The present study seeks to understand if there are differences between the Portuguese and Spanish users’ behavior or perceptions about the consumption of Internet contents in terms of music (or music videos) and films and television series and if such differences are reflected in the age groups. Using the Flash Eurobarometer 437 database, it is identified that age groups is significantly related to the frequency of using the Internet to access music and films online. It is also observed that gender is significantly related to frequency of using the Internet to access films online. The choices facing the Portuguese and Spanish age groups are homogeneous regarding the frequency of Internet use to access music but not films online. These results can be an indication that policies concerning the music and films contents should fit the characteristics of each of these age groups in both countries.